Resolving Macrophages Counter Osteolysis by Anabolic Actions on Bone Cells. (September 2018) - Viniegra, A.; Goldberg, H.; Çil, Ç.; Fine, N.; Sheikh, Z.; Galli, M.; Freire, M.; Wang, Y.; Van Dyke, T.E.; Glogauer, M.; Sima, C.
Progression of inflammatory osteolytic diseases, including rheumatoid arthritis and periodontitis, is characterized by increased production of proinflammatory mediators and matrix-degrading enzymes by macrophages and increased osteoclastic activity. Phenotypic changes in macrophages are central to the healing process in virtually all tissues. Using a murine model of periodontitis, we assessed the timing of macrophage phenotypic changes and the impact of proresolving activation during inflammatory osteolysis and healing. Proinflammatory macrophage activation and TNF-α overproduction within 3 wk after induction of periodontitis was associated with progressing bone loss. Proresolving activation within 1 wk of stimulus removal and markers of resolving macrophages (IL-10, TGF-β, and CD206) correlated strongly with bone levels. In vivo macrophage depletion with clodronate liposomes prevented bone resorption but impaired regeneration. Induction of resolving macrophages with rosiglitazone, a PPAR-γ agonist, led to reduced bone resorption during inflammatory stimulation and increased bone formation during healing. In vitro assessment of primary bone marrow–derived macrophages activated with either IFN-γ and LPS (proinflammatory activation) or IL-4 (proresolving activation) showed that IL-4-activated cells have enhanced resolving functions (production of anti-inflammatory cytokines; migration and phagocytosis of aged neutrophils) and exert direct anabolic actions on bone cells. Cystatin C secreted by resolving but not inflammatory macrophages explained, in part, the macrophage actions on osteoblasts and osteoclasts. This study supports the concept that therapeutic induction of proresolving functions in macrophages can recouple bone resorption and formation in inflammatory osteolytic diseases.